Salmonella and Pathogenic E. coli in the Crop Production Environment: Potential Sources, Survival, and Management - Max Teplitski; Andree George; George Hochmuth (EDIS)
Over the last two decades, at least a dozen major outbreaks of gastroenteritis caused by non-typhoidal Salmonella or enterovirulent E. coli have been linked to the consumption of sprouts, nuts, and fresh (or minimally processed) fruits and vegetables. These outbreaks caught scientists and the public off guard because these pathogens were not previously considered “plant-associated.” This 3-page fact sheet highlights recent discoveries that focus on the ecology of human pathogens in the crop production environment. A better understanding of how pathogens persist outside of animal hosts in agricultural water, soils, and plants will have major impacts on managing produce safety from “farm to fork.” Written by Max Teplitski, Andree George, and George Hochmuth, and published by the UF Department of Soil and Water Science, October 2012.